Disturbance rejection in DOC-out temperature control for DPF regeneration. (March 2017) - Ning, Jinbiao; Yan, Fengjun
Control of diesel oxidation catalyst (DOC) outlet temperature is critical for downstream diesel particulate filter regeneration, but is challenging to control due to the non-minimum phase behavior and varying time delay. To effectively address this issue, a novel and time-efficient composite controller based on modified active disturbance rejection control (mADRC) is proposed for DOC-out temperature control in this paper. The proposed mADRC-based composite controller is a new combination of a model-based feedforward controller and a mADRC with time delay compensation through the mass flow rate of exhaust gas. The model-based feedforward controller is designed to partially compensate the variations of DOC inlet temperature and mass flow rate, while the mADRC is proposed to address the remain disturbances and model uncertainties including time delay uncertainties. Simulation and test results through a high-fidelity Gamma Technologies-Power model demonstrate the effectiveness and robustness of the proposed composite controller in the DOC-out temperature control under steady state and a highly transient new European dynamic cycle (NEDC).